(untitled) (Journal of the College of Basic Education, 2022)
The study of Iranian-Egyptian relations during the presidency of Mohamed Morsi (June 30, 2012 - July 3, 2013) is one of the important studies that cannot be overlooked, especially when passing through the political events that occurred in Egypt at the beginning of the second decade of the twenty-first century , As these events inaugurated a change in its political map, allowing Iran to move towards it according to what its interests require, so it tried to rearrange its cards, bridge its relationship, and adopt a new political approach that differs from the sterile approach since the establishment of its republic in 1979, Which did not result from any understandings regarding the relations between them, as each of the parties had a different political view from the other in most of the events in the Middle East, and when the breezes of political change blew in Egypt, Iran was eager for that action from the first sight, However, she tried to do her best to restore their relationship, extend a helping hand to her, and decipher the jinx in front of the normal return of the relationship between them, to become more sedate and stronger than before, but how was that? And why did Iran initiate moves towards Egypt from the early days of the political change until the arrival of Muhammad Morsi to power? And how did Iranian politicians see the Islamist movement taking over the rule in Egypt? What are the most prominent obstacles that have prevented the return of relations that Iran has built, and finally what is its position on the developments that resulted from the removal of Mohamed Morsi from the presidency? All these questions and others I tried to list their answers through the folds of this study in a historical-analytical manner, to show the reader in general, and researchers in particular, how the Iranian-Egyptian relations took place during the mentioned period.